Making friends with your neighbors: Agglomeration and tacit collusion in the lodging industry - Hernandez, Manuel A.; Gan, Li (National Bureau of Economic Research, 2011)
Agglomeration is a location pattern frequently observed in service industries such as hotels. This paper empirically examines if agglomeration facilitates tacit collusion in the lodging industry using a quarterly dataset of hotels that operated in rural areas across Texas between 2003 and 2005. We jointly model a price and occupancy rate equation under a switching regression model to endogenously identify a collusive and non-collusive regime. The estimation results indicate that clustered hotels have a higher probability of being in the potential collusive regime than isolated properties in the same town. The identification of a collusive regime is also consistent with other factors considered to affect the sustainability of collusion like cluster size, seasonality and firm size, and the results are robust to alternative cluster definitions.